KETIDAKPASTIAN METAFISIKA: KETIDAKJELASAN ONTIK DAN PARADOKS SORITES - Siswadi, Gede Agus; Tantra, Manggala Wiriya (Widya Katambung, 2024)
This research examines the phenomenon of metaphysical uncertainty through two main concepts: ontic vagueness and sorites paradox. Ontic vagueness refers to entities or concepts that do not have clear boundaries or definitions in reality, leading to ambiguity in interpretation and understanding. The sorites paradox, or stack paradox, is a philosophical problem that challenges the boundaries between categories by showing that repeated small changes can produce significant differences, even though there is no clear transition point. By combining these two concepts, this research aims to explore how uncertainty in the structure of reality and language can affect our knowledge and understanding of the world. Through literature analysis and a philosophical approach, this research seeks to identify the epistemological and ontological implications of metaphysical indeterminacy, as well as offer a new perspective on how to deal with and understand indeterminacy in the context of contemporary philosophy. The results of this study are expected to make a significant contribution to the discussion on the foundations of ontology and epistemology, as well as broaden insights into the role of uncertainty in human experience and science.